Pengaruh Strategi Pembelajaran Talking Stick Dan Numbered Heads Together (Nht) Terhadap Hasil Belajar Matematika Ditinjau dari motivasi Belajar Siswa Kelas XII IPSSemester Ganjil di Sma Negeri 1 Mojogedang Tahun 2016/2017 - Ismaida, Afika, Drs. Slamet HW, M.Pd (2016)
This research aim to know, (1) influence of usage of strategy of Talking Stick and of Numbered Heads Together (NHT) to result learn mathematics, (2) influence of motivation learn student to result learn mathematics, (3) interaction between usage of study strategy of Talking Stick and of Numbered Heads Together (NHT) and also motivate to learn to result learn student mathematics. This population of research is entire class student of XI IPS anomalous semester SMA N 1 Mojogedang. Samples in this research use two classes, which is experiment class hit by strategy of Talking Stick and control class hit by strategy of Numbered Heads Together (NHT). The technique intake of sample conducted with technique of cluster sampling random. In this research, researcher use method of test, documentation and questioner.In this research is used by hypothesis test with analysis of variance two way with cell do not be is same. Before to analyses of variance, to do test prerequisite analyses by using method of Liliefors for the test of normality, and use test of Barlet for the test of homogeneity. Result of calculation of data analysis by using level of significance 5% obtained; (1) there are difference of result learn mathematics between given by student is treatment by using approach integrated at method of Talking Stick and method of Numbered Heads Together (NHT) withFα = 5,44 > F0,05;1;58 = 3,998, (2) there are difference of result learn student mathematics evaluated from motivational level learn student with high category, medium category, and lower category, withFb = 3,504> F0,05;2;58 = 3,156 and (3) there is no interaction between method of Talking Stick and method of Numbered Heads Together (NHT) evaluated from motivation learn student to result learn student withFAB = 1,768> F0,05;2;58 = 3,156.